Judicial Perceptions of Media Portrayals of Offenders with High Functioning Autistic Spectrum Disorders - Berryessa, Colleen M. (2014)
In recent years, sensational media reporting focusing on crimes committed by those diagnosed with or thought to have High Functioning Autistic Spectrum Disorders (hfASDs) has caused societal speculation that there is a link between the disorder and violent criminality. No research exists on how and if the judiciary understands and is affected by this coverage. Therefore this study aims to examine how judges perceive and are influenced by media attention surrounding hfASDs and criminality. Semi-structured interviews were conducted with 21 California Superior Court Judges, including questions on media portrayal. Judges perceived general media portrayals of hfASDs in both positive and negative ways. However, almost all judges who had experienced media coverage surrounding hfASDs and criminality identified it as misleading and harmful to public perceptions of the disorder. These findings suggest judges are not exempt from media attention surrounding violence and hfASDs, and they recognize the potential adverse effects of this negative coverage. Although judges' report their opinions are not affected, the results demonstrate that judges are worried that the public and potentially other criminal justice actors are adversely affected and will continue to be moving forward